A review on lithium-sulfur batteries: Challenge, development, and perspective - Shao, Qinjun; Zhu, Shengdong; Chen, Jian (Nano research, 2023)
Lithium-sulfur (Li-S) battery is recognized as one of the promising candidates to break through the specific energy limitations of commercial lithium-ion batteries given the high theoretical specific energy, environmental friendliness, and low cost. Over the past decade, tremendous progress have been achieved in improving the electrochemical performance especially the lifespan by various strategies mainly concentrated on the sulfur cathodes. In this review, the fundamental electrochemistry of sulfur cathode and lithium anode is revealed to understand the current dilemmas. And the advances achieved through diverse strategies are comprehensively summarized, which involves lithium polysulfides (LiPSs) limitation, sulfur redox reaction regulation and electrocatalysis in sulfur cathode and artificial solid electrolyte interface (SEI), electrolyte design, and structured anode in lithium anode. Additionally, the differences between laboratory level coin cells and actual pouch cells need to be addressed that only few reports on practical Li-S pouch cell are available due to the unexpected problems on both sulfur cathode and lithium anode which are masked at lithium and electrolyte excess. Lastly, the challenges and perspective toward the practical Li-S batteries are also offered.